Educação alimentar e nutricional como tema transversal no ambiente escolar - Marcio Antônio Assis Cecotte (2022)
Eating habits are influenced by several factors. Among these, the strong influence of food empires stands out, which promote the replacement of in natura or minimally processed foods with ultra-processed foods. This change in dietary practices, combined with the increase in sedentary lifestyle, has brought several health problems, such as Chronic Noncommunicable Diseases (NCDs). In this scenario, emancipatory food and nutrition education (FNE) is relevant and necessary to face these problems, in which the school presents itself as an indispensable public equipment for FNE actions. Actions that use inclusive methods, allowing the student to be the protagonist in their learning process about adequate and healthy food. Thus, the present work aimed to promote, in addition to improving knowledge on the subject in question, an awareness of students about current food and nutritional problems. This is a study carried out with high school students from a state public school in the city of Ribeirão das Neves-MG, through the application of a didactic sequence (DS), based on the methodology of action research, with an investigative approach. . The effect of DS was evaluated through the application of questionnaires, conversation circles, case studies, analysis of industrialized food labels and evaluation of menus. Several activities relied on the help of digital tools based on information and communication technologies (DICT), and there was even an incentive for students to develop a tool. The results showed that participation in conversation circles, in research, in the use of DICT, in sharing data with their peers and in the development of the application, provided students with the appropriation of scientific knowledge about food and nutrients, their function in the body, the social function of the act of eating, healthy eating. In this way, it is concluded that the students were the protagonists in the construction of their own knowledge, and that the participation and involvement of the students improved from the application of the didactic sequence, awakening them to the adoption of healthier eating practices, aware that The quality of the food we eat directly affects our health.